Green synthesized ZnO nanoparticles using Jatropha curcas latex for antibacterial applications - Yojana Sharma; Vikas Anand; Rajesh Kumar; Anup Kumar; Pawan Heera (Next Materials)
In recent years, zinc oxide nanoparticles (ZnO NPs) have attracted significant interest due to their remarkable antibacterial properties and diverse applications. In the present work, ZnO NPs were prepared through a novel green synthesis approach by using latex of Jatropha curcas plant that act as a bioreducing and stabilizing agent. This environmentally friendly, room temperature synthesis method provides a sustainable alternative for traditional methods by avoiding hazardous chemicals and significant energy consumption. The structural and morphological properties of biosynthesized nanoparticles were examined by using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Scanning electron microscopy (SEM), Energy Dispersive X-ray (EDX), Thermogravimetric analysis (TGA)/Differential thermogravimetric analysis (DTGA), Ultraviolet-visible spectroscopy (UV–VIS), and Raman spectroscopy. From the XRD analysis, the hexagonal wurtzite structure of the prepared material was confirmed with an average crystallite size of ∼ 46.4 nm. The FTIR analysis validated the presence of functional groups. The characteristic peak for ZnO was observed at 491.93 cm−1. From the SEM analysis the average size of the agglomerates and/or aggregates of the primary particles were observed to be ∼ 432 nm. The absorption peak around 375 nm further confirms the formation of ZnO as observed in UV–VIS spectroscopy. The optical band gap of prepared material is found to be 3.30 eV. The EDX analysis confirms the high zinc content in the prepared sample. The thermal stability of the prepared ZnO has been confirmed through TGA analysis. Raman spectroscopy was used to complement the characterization of the ZnO synthesized by green route. The Raman peak with maximum intensity at 431.42 cm−1 can be assigned to the E2High mode, which results from lattice vibrations of zinc and oxygen further confirming the formation of ZnO. The antibacterial properties were studied for three pathogens i.e., Gram-positive Staphylococcus aureus, Bacillus subtilis and Gram-negative Escherichia coli. using the agar well diffusion method. The ZnO exhibited a good zone of inhibition against Gram-positive Staphylococcus aureus with a maximum zone of inhibition of 26 ± 0.5 mm, and demonstrates higher efficacy as compared to chemically synthesized counterparts. This enhanced antibacterial performance is attributed to the synergistic effect of phytochemicals acting as capping agents for the nanoparticles, a feature that is absent from traditional synthesis routes. Furthermore, results reveal that the prepared material via the green route is a wide band gap material which making it a suitable candidate for applications in electronics. Thus, this study not only introduces a sustainable method for ZnO NPs synthesis but also explores their potential as green antimicrobial agents, paving the way for applications in biomedical devices and environmental disinfection.